Volume 5B: Heat Transfer 2015
DOI: 10.1115/gt2015-43012
|View full text |Cite
|
Sign up to set email alerts
|

Ramp Heating in High-Speed Transient Thermal Measurement With Reduced Uncertainty

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. The uncertainty associated with the convective heat transfer coefficient obtained in transient thermal measurement is often high, especially in high-speed flow. The present study demonstrates that the experimental accuracy could be much improved by an actively controlled ramp heating instead of the conventional step-heating approach. A general design guideline for the proposed ramp-heating met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Step heating method (Ma et al. 26 ) is adopted to raise the inlet total temperature T 0,i in a short period. 2 s of the transient thermal measurement data were used for data processing.…”
Section: Experimental Validationmentioning
confidence: 99%
“…Step heating method (Ma et al. 26 ) is adopted to raise the inlet total temperature T 0,i in a short period. 2 s of the transient thermal measurement data were used for data processing.…”
Section: Experimental Validationmentioning
confidence: 99%
“…One default assumption was that the major tip flow structures at high speed condition could be reproduced by a redesigned low speed blade with a matched loading. Wheeler et al [23] reported different flow structures at high and low speed conditions, especially when the tip flow accelerates to a supersonic regime and involves shock structures. However, even without the impact of shock waves on the OTL, it still remains unclear if the conventional scaling method would work for high subsonic conditions.…”
Section: Introductionmentioning
confidence: 99%